Determining the structure of the distillation line diagram for the three-component system α,γ-dichlorohydrin – hydrogen chloride – water - S. M. Zanaveskina; Yu. A. Pisarenko (Тонкие химические технологии)
Ternary vapor-liquid equilibrium (VLE) diagrams provide a graphical tool to predict qualitatively the feasible separations for multicomponent azeotropic mixtures before detailed simulation or experimental study of their distillation. The various graphical representations of the VLE (residue curve and distillation line maps, isotherm map, equilibrium vector field) are closely related and are equally capable of characterizing the mixture. The total information about the ternary system α,γ-dichlorohydrin – hydrogen chloride – water (azeotropy, the boiling temperature of individual substances and singular points) is not available in literature. That is why identification of the distillation line map is a difficult task. Improvement of the distillation line map was made on the base of thermodynamic and topological analyses, simulation of vapor-liquid equilibrium on the base of UNIFAC method and experimental work. Isothermal-isobaric manifold was obtained on the base of experimental work. The boiling points of ternary systems (α,γ-dichlorohydrin – hydrogen chloride – water) were measured accurately at constant pressure using an ebulliometer